2015
DOI: 10.1371/journal.pone.0119355
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Freezing on Faecal Microbiota as Determined Using MiSeq Sequencing and Culture-Based Investigations

Abstract: BackgroundHigh-throughput sequencing has enabled detailed insights into complex microbial environments, including the human gut microbiota. The accuracy of the sequencing data however, is reliant upon appropriate storage of the samples prior to DNA extraction. The aim of this study was to conduct the first MiSeq sequencing investigation into the effects of faecal storage on the microbiota, compared to fresh samples. Culture-based analysis was also completed.MethodsSeven faecal samples were collected from healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
182
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(207 citation statements)
references
References 27 publications
18
182
2
2
Order By: Relevance
“…Distances below 0.05 were not shown extraction yield and the proportions of some genera observed among bacterial communities observed on SWM (Metzler-Zebeli et al 2016). However, it was demonstrated that freezing may only have minor impacts on the global portrait of a bacterial community (Fouhy et al 2015), on which this study focused. The short read lengths (400-440 bp) enabled a thorough taxonomic assignment for all samples at the genus level, with an overall low abundance of 1% of unclassified phyla.…”
Section: Discussionmentioning
confidence: 68%
“…Distances below 0.05 were not shown extraction yield and the proportions of some genera observed among bacterial communities observed on SWM (Metzler-Zebeli et al 2016). However, it was demonstrated that freezing may only have minor impacts on the global portrait of a bacterial community (Fouhy et al 2015), on which this study focused. The short read lengths (400-440 bp) enabled a thorough taxonomic assignment for all samples at the genus level, with an overall low abundance of 1% of unclassified phyla.…”
Section: Discussionmentioning
confidence: 68%
“…PCRs were completed on the template DNA. Initially, the DNA was amplified with primers specific to the V3-V4 region of the 16S rRNA gene which also incorporates the Illumina overhang adaptor (forward primer, 5=-TCGTCGGCAGCGTCAGATGTGTATAAGAGACAGCCTACGGGNGGCWGCAG; reverse primer, 5=-GTCTCGT GGGCTCGGAGATGTGTATAAGAGACAGGACTACHVGGGTATCTAATCC) (36). Each PCR mixture contained DNA template (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Microbial profiling was performed using high-throughput sequencing of the V3-V4 region of the 16S rRNA gene (paired-end reads of 300 bp or 250 bp) on an Illumina MiSeq platform according to the standard Illumina protocol, except that the PCR mix volume was doubled in the first PCR step, and 30 cycles were used instead of 25 (66). Any samples with less than 40,000 postquality reads were removed from the analysis.…”
Section: Figmentioning
confidence: 99%